UTILIZATION OF BLOG AS A MEANS OF PUBLICATION OF STUDENT WRITING IN LEARNING NEWS TEXT WRITING - Rizki Ridha Syahdia; Maya Dewi Kurnia; Riskha Arfiyanti (Cirebon International Conference on Education and Economics Proceeding, 2024)
The background of this study is the tendency of low student interest in learning to write. This raises the interest of the author to make research on digital-based learning media on news text writing material. the purpose of this study was to determine the ability of students in writing news text and to know how the use of blog as a means of publication of Student News Text. The method used in this study is a qualitative descriptive method. Research Data were collected using performance tests, observation techniques, and survey techniques. The data sources used in this study were 53 students of Class XI who had studied news text material. The analysis unit looked at students ' ability to write news texts and the use of blog media as a means of publishing student news texts. The results showed that students have been able to write the text of the news by paying attention to the suitability of the theme and title of the news, the accuracy of the elements of the news, and the suitability of the structure of the news. In addition, the activity of writing news texts using blog media is going well. It is characterized by excellent student response during the learning process. As many as 73.6% of students said that they want to develop a blog that they have as a means of practicing and media publication of their works.